Collaborative versus traditional method validation approach: Discussion and business case - Ray Wickenheiser; Laurel Farrell (Forensic Science International: Synergy, 2020)
For accredited crime laboratories and other Forensic Science Service Providers (FSSPs) performing a method validation can be a time consuming and laborious process, particularly when performed independently by an individual FSSP. In this proposed collaborative method validation model, FSSPs performing the same task using the same technology are encouraged to work together cooperatively to permit standardization and sharing of common methodology to increase efficiency for conducting validations and implementation. FSSPs following applicable standards that are early to validate a method incorporating a new technology, platform, kit, or reagents are encouraged to publish their work in a recognized peer reviewed journal. Publication of validation data provides communication of technological improvements and allows reviews by others that supports the establishment of validity. It also permits other FSSPs to conduct a much more abbreviated method validation, a verification, if they adhere strictly to the method parameters provided in the publication by the original FSSP. By completing this verification, the second FSSP has reviewed and accepts the original published data and findings, thereby eliminating significant method development work. Utilization of published validation data increases efficiency through shared experiences and provides a cross check of original validity to benchmarks established by the originating FSSP. Utilization of the same method and same parameter set enables direct cross comparison of data and ongoing improvements. A business case will be provided to demonstrate the cost savings of the collaborative validation model using salary, sample and opportunity cost bases.